Proximity care pathways and digitalization: opportunities and concerns for medication safety management—Insights from the ProSafe study on community perspectives - Moretti, Francesca; Mazzi, Maria Angela; Montresor, Sara; Colpo, Silvia; Tussardi, Ilaria Tocco; Facchinello, Daniela; Robello, Raffaella; Ambroso, Luigi; Destro, Cristina; Leone, Salvatore; Petruzzelli, Davide; Rimondini, Michela; et al. (Frontiers in Public Health, 2025)
BackgroundEstablishing proximity care pathways, including the digitalization of healthcare, is valuable for sustainable management of Non-Communicable Diseases (NCDs) and Patient-Centered Care (PCC) promotion. However, new safety concerns, particularly in therapy management, may arise. The Community-Based Participatory Research (CBPR) “ProSafe” aims at (i) explore stakeholders’ perspectives on medication safety management in proximity care and (ii) analyze which determinants affect the community’s perspective.MethodsA survey was co-developed with a Patient Safety Council (PSC) and the support of a pharmaceutical company. A purposeful sampling strategy was implemented to recruit individuals aged 18 and older. Data were collected using a dedicated online platform; differences between patients’ and healthy people’s perspectives were explored. Preliminary multiple regression analyses were performed to examine how sociodemographic factors, clinical data and level of digitalization affect outcomes using linear and probit models, accounting for the nature of each outcome variable. The models were combined into multiple equations using a Conditional Mixed Process (CMP) approach.Results417 individuals completed the survey (81.0% affected by a disease). A positive attitude towards shifting therapy administration from hospital to home setting was observed even if a significantly higher proportion of patients compared to healthy individuals raised concerns regarding a potential negative impact on the doctor-patient relationship (47.0% vs. 32.9%, p < 0.01). Additionally, 63.7% of patients reported they would feel less supported in the care process. The usefulness of telehealth, including tele-pharmacy for drug therapy management, was rated higher by healthy individuals compared to patients (mean value 1.3 vs. 1.5 p < 0.01); 43.9% of patients raised concerns regarding the excessive responsibility placed on them in digital care compared to traditional healthcare. Health status and level of education were the variables most frequently associated with significant impacts across multiple outcomes.ConclusionThe community’s perspective on the development of proximity care pathways provided valuable insights into concerns, fears, and limitations that could impact the effectiveness of this important shift in healthcare delivery. Effectively addressing these issues is essential to truly bring disease and medication management closer to patients and their living environments while ensuring that the community becomes co-creators in the implementation of proximity care, fostering health equity and patient autonomy.